IMPROVING THE KNOWLEDGE AND SKILLS OF MOTHERS OF TODDLERS IN ACCOMPANYING THE DEVELOPMENT OF FINE AND GROSS MOTOR SKILLS IN THE GREAT PARENTS SCHOOL EVENT - Wulandari, Ratna Feti; Widhi Sumirat; Nurin Fauziyah; Vide Bahtera (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
The development of Indonesian Human Resources (HR) needs to be carried out in a planned and sustainable manner. The period of five years and under is the golden age for children's intelligence. At the age of 4 years, a child's intelligence capacity has reached 50%, this shows the importance of providing stimulation to early childhood, because it is a foundation that greatly determines of child's further development. Every child has a different level of motor development. Children's motor development has an important role in their lives. One important aspect of the process of child development at preschool age is motor development, because motor development is the child's intelligence and social emotions. The purpose of this Community Service is to increase the knowledge and skills of parents in training gross and fine movements to children so that later children can be more skilled and careful in using their fingers when doing practical things in everyday life, school such as writing, painting and others. The method in this Community Service is to use counseling with active lectures, practice detecting children's motor development and evaluation using questionnaires. The media used are power point, child development cards (KKA). The results of this Community Service There is an increase in the knowledge of mothers of toddlers, namely from 50% in the sufficient category to 55% in the good knowledge category. and the mother's skills can be seen from the mother being able to train gross and fine motor skills in her child by filling in the child's development card.